Envolvimento, busca online e visitas a lojas físicas: o consumidor no varejo da moda - Silva, Eric Ferreira (2023)
The Covid-19 pandemic has forced many people to transact online and communicate in a more digital way; the pace of population digitization has accelerated. Social distancing has changed consumption habits and boosted the online search for products (goods and/or services). Even so, many products continued to be consumed in person, due to the nature of production and/or delivery and/or consumer preference. This dissertation investigates and analyses, in fashion retail, the effect of consumer Involvement with physical stores on the Attitude towards online search for information about these stores, Subjective Norms, Intention to Visit and Visit to physical stores. I review the literature to elaborate hypotheses and a conceptual model. I tested this framework with a quantitative survey in an online survey, using variance Structural Equation Modeling. In the sample of consumers in Brazil, where the influence of Involvement in this Attitude was found, which in turn, together with the corresponding Subjective Norms, influence the Intention to visit physical stores, increasing the possibilities of visiting such stores in person.